2009
DOI: 10.1128/jvi.01752-08
|View full text |Cite
|
Sign up to set email alerts
|

Leader-Induced Phosphorylation of Nucleoporins Correlates with Nuclear Trafficking Inhibition by Cardioviruses

Abstract: Picornaviruses disrupt nucleocytoplasmic trafficking pathways during infection. Poliovirus and rhinovirus inhibit nuclear protein import/export through a series of 2A protease-dependent cleavages within nuclear pore proteins (nucleoporins [Nups]), including Nup62, Nup98, and Nup153. Cardioviruses lack the same protease and instead affect trafficking inhibition through an activity mapped to their leader (L) protein, a 67-to 76-amino acid (aa) polypeptide with no known enzymatic activity. We have shown that L fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 38 publications
4
130
0
Order By: Relevance
“…Once in the nucleus, the hnRNP A1⅐Trn-1 complex is disassembled by RanGTP (67). Several viruses interfere with these processes via degradation of nucleoporins and a disruption of Trn-1 function (45, 68 -70) or by directly modulating Nup62 function (71,72). We found that, although the other FG repeat-containing Nup98 proteins were unaffected, the abundance of Nup62 was reproducibly decreased (Fig.…”
Section: Hiv-1-induced Cytoplasmic Accumulation Of Hnrnp A1 Is Causedmentioning
confidence: 72%
“…Once in the nucleus, the hnRNP A1⅐Trn-1 complex is disassembled by RanGTP (67). Several viruses interfere with these processes via degradation of nucleoporins and a disruption of Trn-1 function (45, 68 -70) or by directly modulating Nup62 function (71,72). We found that, although the other FG repeat-containing Nup98 proteins were unaffected, the abundance of Nup62 was reproducibly decreased (Fig.…”
Section: Hiv-1-induced Cytoplasmic Accumulation Of Hnrnp A1 Is Causedmentioning
confidence: 72%
“…Instead, Ran:L E binding is leveraged by consequent activation of a potent Nup phosphorylation cascade, the true cause of trafficking inhibition. This inhibition happens in infected cells even before the virus begins to replicate (6,26). The cascade involves Erk1/2 and p38 kinases and is absolutely dependent on Ran:L E interactions and also on the dual phosphorylation of L E itself, an activity that is a prerequisite, and not a consequence, of the Nup modifications (7,10,15,16,27).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant L E -GST (EMCV) and mutated derivatives were expressed and purified from Escherichia coli as previously described (6,15,24). GST-L M (Mengo) has also been previously described (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, NPC destabilization may result from the association of Nups and integrated proviral cDNA or nuclear vRNA during transcription (Capelson et al, 2010;Hou and Corces, 2010;Strambio-De-Castillia et al, 2010). HIV-1 may disrupt NPCs to evade antiviral responses, as seen in other viruses (Gustin and Sarnow, 2002;Fontoura et al, 2005;Bardina et al, 2009;Porter and Palmenberg, 2009;Atasheva et al, 2010;Ren et al, 2010). Another possibility is that encapsidated Nup62 may be required for efficient delivery of the PIC into the nuclei of newly infected cells (Fig.…”
Section: Nup62 Is Essential For Hiv-1 Vrna Exportmentioning
confidence: 99%